2007
DOI: 10.1007/s11136-007-9249-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among Turkish immigrants in Sweden

Abstract: Turkish immigrants' quality of life perceptions were better than those of the Turkish sample. The best scores were received from the third generation. The first generation and female immigrants need attention in order to receive higher quality of life perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
6
28
2
Order By: Relevance
“…Though previous studies have reported the correlations of immigrants’ age, sex and marital status with their QOL (Thoman and Surís 2004; Bayram et al 2007; Pantzer et al 2006; Zhang et al 2009) in both bivariate and multiple regression analyses, however, these correlations were not observed in this study. Although correlation was found between immigrants’ age and the environment domain of QOL, and between marital status with the overall QOL in bivariate analyses, these associations disappeared in the multiple regression analysis due to the crowding out effects.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Though previous studies have reported the correlations of immigrants’ age, sex and marital status with their QOL (Thoman and Surís 2004; Bayram et al 2007; Pantzer et al 2006; Zhang et al 2009) in both bivariate and multiple regression analyses, however, these correlations were not observed in this study. Although correlation was found between immigrants’ age and the environment domain of QOL, and between marital status with the overall QOL in bivariate analyses, these associations disappeared in the multiple regression analysis due to the crowding out effects.…”
Section: Discussioncontrasting
confidence: 77%
“…Although our study samples reflect the real gender and marital status distribution of the immigrant population, the result of this study cannot be generalized to male immigrants, as well as single and married Chinese immigrants in Hong Kong. Since previous studies found that marital status associated with immigrants’ QOL (Zhang et al 2009; Bayram et al 2007), and QOL of male immigrants was found to be higher than that of females (Bayram et al 2007), therefore, studies of male immigrants and single Chinese new immigrants in Hong Kong must be conducted in the future so that these issues can be addressed.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a review of the research literature on quality of life (QOL) indicated a lack of consensus over its operational definition and use of terminology [3], the concept of QOL is being used increasingly in behavior and clinical research to measure perceived well-being among various vulnerable populations, such as migrants, refugees, and various patients [1,2,5]. The term ''quality of life'' evolved from the constructs of life satisfaction and subjective well-being and represented the individual's overall satisfaction or happiness.…”
Section: Introductionmentioning
confidence: 99%